Ethanol Level of Vitreous Fluid in Road Accident fatalities referred to Tehran Legal Medicine Center in 2018 - Najjari, Fars; Sajjadi, Sara; Emamhadi, MohammadAli (Archives of Men's Health, 2020)
Background: High risk behaviors such as substance use are among the human factors that can play an important role in fatal road accidents and deaths. Objective: To determine the status of alcohol consumption based on vitreous fluid exam in cadavers sent to Tehran Legal Medicine Organization. Materials and Methods: In this descriptive analytical cross-sectional study, all fatalities sent to the Tehran Legal Medicine Organization during 2018 were studied. A vitreous sample was used to measure the amount of alcohol. Results: Out of 676 cadavers (85% male; mean age 40.6±6.45), the toxicology results for alcohol was positive in 6.51% (91% male; mean age 37.10±15.7). There was a significant difference between the two sexes (P < 0.00) and the educational level (P1< 0.00). Most fatal accidents occurred in positive toxicology cases between 10-12 pm and on Fridays followed by Thursdays. Conclusion: The policy of non-consumption of alcohol based on Islamic teachings in Iran has played an important role in significantly reducing fatal accidents caused by alcohol.